GOVERNMENT POLICIES IN DRIVING LOCAL AND NATIONAL ECONOMIC GROWTH AND THEIR IMPACT ON STATE REVENUE THROUGH TAXES AND LEVIES - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Economic growth is one of the main indicators of a country's development success, both at the local and national levels. The government plays a strategic role in driving this growth through fiscal and monetary policies, infrastructure development, strengthening the productive sector, and empowering MSMEs. Synergy between central and regional policies is a key factor in creating inclusive, sustainable, and equitable growth across regions. This study uses a literature review method by analysing various academic sources, official government publications, and research reports related to the relationship between government policies, economic growth, and state revenue. The results of the study show that positive economic growth can expand the tax base, increase state revenue through income tax, value-added tax, local taxes, and levies. In addition, equitable growth contributes to an increase in local revenue, which supports fiscal independence. To optimise the contribution of economic growth to tax and fee revenue, adaptive and integrative policies are needed, along with tax reforms that emphasise broadening the tax base, digitalising services, and improving taxpayer compliance. These findings confirm that the integration of economic and fiscal policies is a determining factor in strengthening the capacity for national development financing and improving public welfare.